Occupational and environmental influences on the development and course of lupus - Cooper, Glinda (Henry Stewart Talks, 2007)
Role of genetic susceptibility in the etiology of systemic lupus erythematosus (SLE), Demographic risk factors for SLE, Epidemiologic and experimental research on occupational exposures (respirable silica dust and solvents) and risk of developing SLE, "Lifestyle" factors (smoking, use of hair dyes) and risk of developing SLE, Ultraviolet radiation and risk of developing SLE, Research on exposures and SLE severity (disease activity and damage), Examples of specific gene-environment interactions, Environmental pollutants and SLE
Archived at 2015/09/17